Isolation and characterization of cellulose nanofibers from argentine tacuara cane (Guadua angustifolia kunth) - Rodriguez Ramirez, Carlos Alejandro (2018)
New trends in the area of material improvement are the use of natural nano-charges from renewable biomass, improving the value and sustainability of our country’s natural products. Bamboo is widely used in many countries of the world, although in Argentina, despite being commercialized and exported for the manufacture of wood floors, it goes unnoticed despite having native species. Therefore, researchers identified the native and exotic species present in our country and are working on novel uses. In this context, it is proposed the Argentine Tacuara Cane (Guadua Angustifolia Kunth), endemic plant as a new source of nanocellulosic materials, where stem fibers have been isolated using a green method achieving with yield of 45.9% of cellulose. The cellulose nanofibrils (CNF) were obtained using a green homogenization method. The CNF exhibited web-like long fibrous structure with the diameter of 10-20 nm. The crystallinity was 65.5%, as for the onset temperature of thermal decomposition was 212°C. The nanocellulose isolated from the Tacuara Cane seed fibers has a high potential to be used as a new source of cellulose-based nanofiller for the reinforcement of bionanocomposite films.